The story of Ai Fen, Li Wenliang and Zhang Jixian at the beginning of COVID-19 pandemic - Pamo-Reyna, Oscar G. (2020)
The figure of the Chinese doctor LiWenliang has permeated public opinion as the first to alert his colleagues about the appearance of a new unknown disease with epidemic characteristics and for that reason he was sanctioned by the Chinese authorities. However, there are two other stories behind Li  Wenliang: Ai Fen, the doctor who really was the one who alerted others about the nascent epidemic  and Zhang Jixian, who was officially the first doctor who alerted about the birth of COVID-19. Keywords: Li Wenliang, Ai Fen, Zhang Jixian, history, COVID-19, coronavirus, pandemic, China.